From District to Municipality: a preliminary assessment of the process of creating districts in Minas Gerais in the period 2014-2021 (Revista Espinhaço, 2024)
The article analyzes the process of creating districts in Minas Gerais in recent years. It highlights the period 2014-2021, when 165 new districts were created, a figure that represented a growth of 516% compared to that recorded in the previous eight years. As during the period there was no change in the legislation pertinent to the creation of districts, and the intensity of the process in Minas Gerais was not accompanied by the same movement in the other states of the Federation, the search for possible explanations focused on specific state processes that could encourage such a rush. The research result indicates that the Programa Minas Comunica II, implemented by the State Government between 2014 and 2020, with the aim of expanding mobile telephone service in Minas Gerais villages, became an instrument to encourage the creation of new districts in Minas Gerais.
Keywords: Municipalism; Creation of districts; Minas Gerais; Public Policies